2019
DOI: 10.1002/jcb.29291
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA Alu‐mediated p21 transcriptional regulator promotes proliferation, migration, and pipe‐formation of human microvascular endothelial cells by sponging miR‐126

Abstract: Peripheral artery disease (PAD) is a serious hazard to the elderly in the lower extremity atherosclerotic plaque, accompanied by a large number of angiogenesis. Long noncoding RNA Alu-mediated p21 transcriptional regulator (APTR) exerts important functions in promoting cell growth. Therefore, we planned to research the mechanism of APTR in angiogenesis in PAD. CCK-8 assay, flow cytometry analysis, and migration assay were to detect cell viability, apoptosis, and migration respectively. The interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Experimental studies have also found that lncRNAs can regulate EC gene expression; for instance, lncRNA-CCL2 upregulates the levels of its adjacent CCL2 gene, which is a pro-atherosclerotic chemokine gene in the EC lines. Further, the lncRNA APTR can promote the proliferation and migration of ECs ( 67 ). HULC can promote the apoptosis of ECs ( 35 ).…”
Section: Lncrna and Rbp As Regulators Of Atherosclerosismentioning
confidence: 99%
“…Experimental studies have also found that lncRNAs can regulate EC gene expression; for instance, lncRNA-CCL2 upregulates the levels of its adjacent CCL2 gene, which is a pro-atherosclerotic chemokine gene in the EC lines. Further, the lncRNA APTR can promote the proliferation and migration of ECs ( 67 ). HULC can promote the apoptosis of ECs ( 35 ).…”
Section: Lncrna and Rbp As Regulators Of Atherosclerosismentioning
confidence: 99%
“…For example, APTR can recruit PRC2 to the p21 promoter of malignant glioma cells to inhibit p21 expression and accelerate tumor progression. 11 Silencing APTR in osteosarcoma cells inhibits cell proliferation, invasion, and migration. 12 APTR promotes the proliferation of leiomyoma cells by targeting the Era Wnt pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) (> 200 nucleotides) are a class of RNA transcripts that can regulate gene expression but cannot code protein (Bu et al, 2012;Kung et al, 2013). LncRNAs have been reported to play a role in a variety of biological pathways (Jiapaer et al, 2018;Song et al, 2019) and disease states (Kung et al, 2013), including tumors (Gutschner and Diederichs, 2012). Recently, the role of lncRNAs in osteosarcoma pathogenesis has attracted much attention and is being heavily investigated, particularly through high-throughput sequencing.…”
Section: Introductionmentioning
confidence: 99%